Quality Yoghurt Set with the Addition Lactobacillus acidophilus FNCC 0051 and Streptococcus thermophilus FNCC 0040 Encapsulated in Terms of pH, Total Titrated Acid, Syneresis, and Total Lactic Acid Bacteria - Wulandasari, Devia; Al Awwaly, Khothibul Umam; Manab, Abdul (Universitas Halu Oleo, 2022)
Probiotics are generally added in the manufacture of food products because of their function that can provide benefits to human health, especially in the digestive tract. The probiotics used in this study were Lactobacillus acidophilus FNCC 0051 and Streptococcus thermophilus FNCC 0040 which were encapsulated and added in making yoghurt sets. The purpose of this study was to examine the physicochemical and microbiological quality of the yoghurt set with the addition of encapsulated Lactic Acid Bacteria (LAB). The research method used is a laboratory experiment using a completely randomized design (CRD) pattern with 4 treatments and 3 replications. The treatments given were P0 Addition of LAB without encapsulation (control) (2%); T1 addition of 2% encapsulated LAB (v/v); T2 added 3% encapsulated LAB (v/v) and T3 added 4% (v/v) encapsulated LAB. Data analysis used Analysis of Variance (ANOVA). The results of the analysis showed that the encapsulation using gelatin and Na alginate coatings gave a very significant difference (P<0.01) to the syneresis of yoghurt sets with the resulting average T0 (24.51±0.70%), T1 (23.52±0.76%), T2 (20.44±0.44%), and T3 (19.96±0.83), a significant difference (P<0.05) on the pH of the yoghurt set with the resulting average T0 (4.56±0.03), T1 (4.55±0.02), T2 (4.45±0.09), and T3 (4.40±0.07), a significant difference (P<0.05) to the total acid titrated yoghurt set with the resulting average, namely P0 (0.68±0.14%), T1 (1.05±0.03%), T2 (1.13±0.32%), T3 (1.31±0.21%), the significant difference (P<0.05) on the total LAB yoghurt set with the resulting average T0 (8.62±0.30 log CFU/ml), T1 (9.20±0.70 log CFU/ml), T2 (9.36±0.33 log CFU/ml), and T3 (9.51±0.10 log CFU/ml). It was concluded that the addition of the percentage of encapsulated LAB of 4% was able to improve the quality of the yoghurt set optimally.Keywords: yoghurt set, probiotics, encapsulation, pH, total acid, syneresis, total LAB